Analytical Modeling and Simulation of Heat Recovery Steam Generator in a Cogeneration Plant - Baheta, Aklilu Tesfamichael (2009)
The heat recovery steam generator (HRSG) system, which is part of the cogeneration plant, produces steam by utilizing the heat from the gas turbine exhaust gas. The gas turbine performance is affected by load and ambient conditions. This can affect the exhaust gas condition leaving the gas turbine like temperature and flow rate that enter into the HRSG. And they in turn affect the HRSG performance. So, adequate considerations must be given to predict the HRSG performance that varies with changes in the gas turbine operation. For that mathematical modeling and simulation is a useful tool. Hence, based on the HRSG components the steady state modeling and a program to predict the off-design characteristics of the HRSG were developed. The design and off-design points of the HRSG were analyzed with a special focus on the estimation of the performance prediction of the HRSG. The HRSG simulation is proven to be additional tool for better prediction of the cogeneration process, parameters such as steam generation and HRSG performance at different operational conditions of the gas turbine. The modeling in the present work allows good temperature profile optimization.